2022
DOI: 10.1063/5.0097172
|View full text |Cite
|
Sign up to set email alerts
|

Local anisotropy control of Pt/Co/Ir thin film with perpendicular magnetic anisotropy by surface acoustic waves

Abstract: The control of perpendicular magnetic anisotropy (PMA) in thin films by strain has considerable potential for energy-efficient information storage and data processing. Here, we report on the control of PMA in Pt/Co/Ir thin films by the strain produced by standing surface acoustic waves (SAWs). A significant (∼21%) coercivity reduction (from 4.80 ± 0.03 to 3.80 ± 0.02 mT) can be obtained by applying a standing SAW with a center frequency of 93.35 MHz. Furthermore, the standing SAWs induce a greater-than 11-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, to operate any of these devices in an energy-efficient manner, it is increasingly recognised that alternatives to magnetic field or electric current must be used. Magnetoelectric methods that use electric field to modify exchange coupling or magnetic anisotropy have been demonstrated to control domain walls, and are considered to be low-energy due to the lack of current flow and therefore minimal Joule heating [6,7,8]. Strain applied via a voltage-controlled piezoelectric, for example, modifies the magnetic anisotropy and has the advantage of allowing reversible control of magnetic properties of a multilayer with PMA, including domain wall dynamics [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, to operate any of these devices in an energy-efficient manner, it is increasingly recognised that alternatives to magnetic field or electric current must be used. Magnetoelectric methods that use electric field to modify exchange coupling or magnetic anisotropy have been demonstrated to control domain walls, and are considered to be low-energy due to the lack of current flow and therefore minimal Joule heating [6,7,8]. Strain applied via a voltage-controlled piezoelectric, for example, modifies the magnetic anisotropy and has the advantage of allowing reversible control of magnetic properties of a multilayer with PMA, including domain wall dynamics [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, SAW-driven FMR is at the heart of the acoustic control of magnetism and spin current, [4][5][6] including SAW-induced magnetization switching, [7][8][9] SAW-assisted spin-transfer torque, [10,11] and spin-orbit torque switching, [12] SAW-controlled spin texture creation and motion. [13][14][15][16][17][18] Meanwhile, integrating magnetism manipulation into SAW systems also provides a new approach for designing miniaturized RF devices such as isolators and circulators.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, SAW‐driven FMR is at the heart of the acoustic control of magnetism and spin current, [ 4–6 ] including SAW‐induced magnetization switching, [ 7–9 ] SAW‐assisted spin‐transfer torque, [ 10,11 ] and spin‐orbit torque switching, [ 12 ] SAW‐controlled spin texture creation and motion. [ 13–18 ] Meanwhile, integrating magnetism manipulation into SAW systems also provides a new approach for designing miniaturized RF devices such as isolators and circulators. The key is to realize nonreciprocal SAW propagation, which can be achieved by the interference of shear‐ and longitudinal‐type magneto‐elastic couplings, [ 19–21 ] asymmetric spin wave dispersion via Dzyaloshinskii‐Moriya interaction [ 22,23 ] or ferromagnetic multilayers, [ 24–27 ] magneto‐rotation coupling, [ 28 ] and phonon angular momentum transfer.…”
Section: Introductionmentioning
confidence: 99%
“…18 The dynamic strain induced by surface acoustic waves (SAWs) has also been suggested as an attractive approach to control thin film magnetization. [19][20][21][22][23][24][25][26][27][28][29][30][31] In particular, Yokouchi et al experimentally observed the creation of skyrmions by SAWs in a Pt/Co/Ir thin film owing to the inhomogeneous effective torque arising from both SAWs and thermal fluctuations via magnetoelastic coupling. 32 Nepal et al theoretically studied the dynamical pinning of skyrmion bubbles at the anti-nodes of standing SAWs in a FePt nano-wire, revealing the strain gradient induced by SAWs is the driving force for skyrmion motion.…”
mentioning
confidence: 99%